2012
DOI: 10.1073/pnas.1211717109
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of lymph node transit times reveals differences in antigen surveillance strategies of naïve CD4 + and CD8 + T cells

Abstract: Naïve T cells continually recirculate between blood and secondary lymphoid organs, scanning dendritic cells (DC) for foreign antigen. Despite its importance for understanding how adaptive immune responses are efficiently initiated from rare precursors, a detailed quantitative analysis of this fundamental process has not been reported. Here we measure lymph node (LN) entry, transit, and exit rates for naïve CD4 + and CD8 + T cells, then use intravital imaging and mathematical modeling to relate cell-cell intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(150 citation statements)
references
References 40 publications
6
144
0
Order By: Relevance
“…Although the molecular details are not yet known, it is tempting to speculate that thymic assortment and peripheral response mode share a molecular basis. The theme of higher dependency on MHCderived signals extends to naive CD4 + T cells that traverse LNs in an MHC-dependent manner and adjust CD5 levels to TCR affinity, whereas CD8 + T cells do not (49,70). In addition, the CD4 + T memory cells recirculate more freely through tissues, while their CD8 + counterparts are confined in an Ag-independent way at the infection site (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular details are not yet known, it is tempting to speculate that thymic assortment and peripheral response mode share a molecular basis. The theme of higher dependency on MHCderived signals extends to naive CD4 + T cells that traverse LNs in an MHC-dependent manner and adjust CD5 levels to TCR affinity, whereas CD8 + T cells do not (49,70). In addition, the CD4 + T memory cells recirculate more freely through tissues, while their CD8 + counterparts are confined in an Ag-independent way at the infection site (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…Mandl et al 36 have recently shown that interactions with MHC class II molecules retained CD4 T N cells in LNs. By using the same protocol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD5 expression on CD4 T N cells has been shown to be adjusted to reflect TCR contact with self [34][35][36][37] . In fact, the more a CD4 T N cell interacts with self, the more this cell expresses CD5.…”
Section: Resultsmentioning
confidence: 99%
“…This, however, does not rule out the possibility that CD5 surface levels may be dynamically tuned in response to self-pMHC availability [23]. The loss of sub-threshold TCR signalling upon the abrogation of the interaction of T cells with MHC leads to a decrease in CD5 levels [21,24]. Therefore, CD5 levels may be a function of the net signal obtained from self-ligands which will depend on TCR avidity as well as the presence of competing T cells "consuming" the same available ligand.…”
Section: Increased Lip Of Cd4 + T Cells With Greater Self-pmhc Reactimentioning
confidence: 99%